2022
DOI: 10.3389/fpls.2022.1021337
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal trends in the structure, similarity and beta diversity of plant communities invaded by Alternanthera philoxeroides in heterogeneous habitats

Abstract: Variations in latitudinal gradients could lead to changes in the performance and ecological effects of invasive plants and thus may affect the species composition, distribution and interspecific substitution of native plant communities. However, variations in structure, similarity and beta (β) diversity within invaded communities across latitudinal gradients in heterogeneous habitats remain unclear. In this study, we conducted a two-year field survey along 21°N to 37°N in China, to examine the differential eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…From July to August of 2019-2021, the time of year during which the growth period of plant species is vigorous, we selected sites that were invaded by A. philoxeroides over an area of more than 100 m 2 to set the sampling plots, and the plots contained low (A. philoxeroides coverage < 40%), moderate (A. philoxeroides coverage was 40%-60%) and heavy (A. philoxeroides coverage > 60%) invaded levels. Starting from 21 N-37 • N) [34,36,39]. Five terrestrial plots were set along each latitudinal cluster, and five aquatic plots were also set in areas with similar habitat conditions along the same latitudinal cluster [35].…”
Section: Site Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…From July to August of 2019-2021, the time of year during which the growth period of plant species is vigorous, we selected sites that were invaded by A. philoxeroides over an area of more than 100 m 2 to set the sampling plots, and the plots contained low (A. philoxeroides coverage < 40%), moderate (A. philoxeroides coverage was 40%-60%) and heavy (A. philoxeroides coverage > 60%) invaded levels. Starting from 21 N-37 • N) [34,36,39]. Five terrestrial plots were set along each latitudinal cluster, and five aquatic plots were also set in areas with similar habitat conditions along the same latitudinal cluster [35].…”
Section: Site Selectionmentioning
confidence: 99%
“…Neutral theory states that species similarity rather than species difference contributes to high community diversity; thus, continuous biointeractions among multiple species in terrestrial A. philoxeroides communities promote coexistence groups with high niche similarity [49]. In addition, Wu et al (2022) found that A. philoxeroides invasions caused higher community homogenization in terrestrial habitats than in aquatic habitats, and functional groups of Gramineae and Compositae that have strong invasion resistance widely exist in the community [34], which causes the plant species in terrestrial habitats to have closer geographical affinity and facilitates their convergent evolution. Moreover, environmental filtering caused by strong disturbances (e.g., human disturbances and insect feeding) in terrestrial habitats have led to the repeated colonization of plant species in the same species pool, which have caused similar species to show obvious aggregation and thus facilitated the coexistence of species with high niche similarity [19].…”
Section: Causes Of Niche Characteristic Formation In Heterogeneous Ha...mentioning
confidence: 99%
See 2 more Smart Citations